IMPLEMENTATION OF THE 2013 CURRICULUM IN MATHEMATICS LEARNING IN CLASS IV AT SDN TALABIU DISTRICTS WOHA, BIMA REGENCY - Nurhoyati Nurhoyati; Ita Fitriati; Mariamah Mariamah (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
This research is motivated by the latest regulations on the revised edition 2013 which are new in planning, in which mathematics becomes a self-supplemented subject and is not integrated with other subjects. This type of research is field research (field research) by discussing qualitative, data collection techniques with observation, interviews and documentation, while analyzing the data using the Miles Huberman analysis model, namely: data reduction, data presentation, and verification data. The results of the study show how the teacher steps in compiling the lesson plan that is choosing learning, reviewing the teacher's book, studying the syllabus, then compiling the lesson plan. The RPP prepared by the teacher is in accordance with the concept of the 2013 curriculum. In the implementation of learning in the 2013 curriculum, the teacher has used learning by using scientific learning, and a learning model that is in accordance with the concept of the 2013 curriculum. student knowledge and skills. Authentic assessment used by teachers includes discussion, performance, and written.